The Criteria for Evaluating the Quality of Rural Spaces and Settlements (مسکن و محیط روستا)
The criteria of quality in human settlements, which pave the way for evaluation of the settlements and spaces, have been studied for few decades in the literature of Urban Design. So many viewpoints are available in this regard. Rural settlement as a kind of human settlements has its own physical, environmental, social, cultural, economical characteristics. The differences between rural and urban areas mean that we should think about presenting different items for evaluation of rural areas and the settlements. The most important target of this article is to achieve the major quality components and criteria in the rural spaces and the settlements. The main reason for raising this research is lack of reliable theories about evaluation of quality in rural spaces and the settlements. The only choice is using the ideas of urban and landscape design to complete rural design researcher's ideas. We used descriptive and analytical research methods and qualitative and quantitative analysis of the quality criteria in these various views in order to identify evaluation criteria of spaces and the settlements. The result is a hierarchical list of classified criteria for quality in an acceptable human settlement. Most of these criteria are true in rural spaces and settlements and a few do not fit with the rural character and environment. The most important criteria are the identity and sense of rural place, sustainability, durability, and paying attention to the natural and man-made context in the field of physical and aesthetic components social livability and solidarity, and paying attention to social and cultural context in the field of social and cultural components vitality and survival of native economy in the field of functional components efficiency in energy and resources usage, connection with the nature, and avoidance from polluting the environment in the field of environmental components participation in the design and implementation in the field of management components. The last point is: each village and every rural area has a unique character. So, presenting a general idea for a variety of these areas is so difficult. This article is accounted as the first step, and should be completed in the future.